Izkušnje revidenta, preglednika in projektanta s področja jeklenih konstrukcij - Hladnik, Leon (Gradbeni vestnik, 2018)
The article presents personal experiences gained in many years of professional activity as a reviewer, surveyor and designer in the field of building steel structures. Some less relevant or inadequate practices that should be improved or changed are shown. These personal experiences could be taken into account in the elaboration of a new rulebook on More detailed contents of the project documentation and Professional rules on the basis of the new Building Act.
Keywords: building structures; designer; gradbene konstrukcije; jeklene konstrukcije; preglednik; projektant; revision; revizija; steel structures; surveyor